Joint activity of higher school teachers from psychological and pedagogical aspects - S V Viktorenkova (Peoples' Friendship University of Russia (RUDN University), 2009)
Article is devoted a problem of the organization of effective joint activity of high school teachers. The questions of the role of joint activity of teachers in quality of teaching are considered. There is the system analysis of concept «joint activity» from psychological and pedagogical aspects.